Effects of temperature and tomato variety on development stages of Bactericera cockerelli (Sulc) (Hemiptera: Triozidae) - Haidel Vargas-Madriz (Acta Zoológica Mexicana (nueva serie), 2020)
Tomato is one of the most consumed vegetables per capita in the world; it is grown both in the open and in greenhouses. Under these conditions, the pest is considered a severe problem, especially considering Bactericera cockerelli Sulc. Therefore, in this experiment, the life history of this pest insect in two tomato varieties: “Charanda F1” and “Rafaello” the differences in the development stages of the insect, the mean temperatures of two cycles, and the accumulated heat units determined. The work consisted of evaluating the development of the instars of B. cockerelli during two crop cycles in both varieties, as well as the accumulation of heat units to differentiate the distinct instars. The insect populations developed in the Rafaello variety had shorter lives and showed a higher death rate of eggs than did those that developed in Charanda F1. The temperature was another determining factor; when the temperature remained low, the insect biological cycle was longer. Likewise, heat units were different between the two varieties; in Rafaello, 598.13 heat units needed while in Charanda F1, only 464.98. The differences may be due to the morphological characteristics of each variety, as the presence of trichomes and oils. Thus, we suggest that these variables studied in future research works.